The Effect of Hot-Melt Extrusion of Mulberry Leaf on the Number of Active Compounds and Antioxidant Activity - Hyun-Bok Kim; Suji Ryu; Jong-Suep Baek (Plants, 2022)
The aim of this study is to compare the functions of the physiologically active compounds of three types of mulberry leaf by cultivar, and to confirm the changes using hot-melt extrusion (HME−ML). The active components of mulberry leaf were analyzed using the HPLC system, and total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity were measured. Among the three varieties, the highest contents of rutin and isoquercetin were detected in Cheongil, of TPC in Cheongol, and of TFC in Cheongil. It was confirmed that this bio-accessibility was increased in HME−ML compared with the control. The DPPH radical scavenging activity of Cheongol showed greater antioxidant properties, and HME showed improvement in the antioxidant properties of all mulberry leaves. These results suggest that the application of HME technology can improve the biological activities of mulberry leaf.